Effects of single- and mixed-bacterial inoculation on the colonization and assembly of endophytic communities in plant roots - Zhang, Ting; Xiong, Juan; Tian, Rongchuan; Li, Ye; Zhang, Qinyi; Li, Ke; Xu, Xiaohong; Liang, Lianming; Zheng, Yi; Tian, Baoyu (Frontiers in Plant Science, 2022)
In this study, 55 bacterial strains randomly isolated from tomato plants were selected and separately inoculated to wheat seeds in plate experiment. Most of the isolated bacterial strains showed their ability to produce IAA and promote plant growth. The results showed that bacterial inoculation had a significant effect on the community composition and bacterial diversity of wheat root endophytic microbiome. The wheat root samples with single bacterial inoculation were significantly separated into two groups (A and B) with differential community structure and composition. Most of root samples (Group A) were predominated by.one or a few of bacterial species, mainly belonged to Enterobacter, Bacillales or Rhizobiales. In contrast, only a few root samples (Group B) were first colonized by abundant bacterial groups with a higher bacterial diversity. However, in most case, bacterial inoculation would not result in the bacterial colonization in wheat root, even for the dominant bacteria isolated form tomato. CAP analysis demonstrated that the variation and difference among the endophytic communities of wheat roots were significantly related to the taxonomic status and lignocellulose-degrading enzymes of the inoculated bacterial strains (p < 0.05). Further experiment about the mixed bacterial inoculation showed that the plant roots were colonized by a more diverse and abundant bacterial communities. To further demonstrate the role of lignocellulose-degrading enzymes for the bacterial colonization in plant roots, four strains with different colonization abilities were selected for transcriptome sequencing analysis.All of them were annotated to Starch and sucrose metabolism pathway. However, when comparing the pathway of Bac_133, Bac_71 with Ent_181, Ent_189, we find that the expression of lignocellulase-decomposing enzyme in the pathway and its annotation was down-regulated and the difference between them was extremely significant (p<0.05). In addition, we also found that most of them not only become the dominant bacteria in the wheat infection experiment, but also the dominant populations of tomato root endophytic bacteria, indicating that there is a certain certainty that bacteria become endophytic bacteria. In general, our result demonstrated that lignocellulose decomposing enzyme played a vital role for the bacteria to become the endophytes and their success to colonize in root tissues.